PROGRAMA DE SAÚDE PÚBLICA JUNTO A UM EDUCANDARIO - Andrade, Odete Barros de (Arquivos da Faculdade de Higiene e Saúde Pública da Universidade de São Paulo, 1966)
This is the partial presentation of a health program planned and carried on by the Nursing Service of the Health Center of the School of Public Health - University of São Paulo, Brazil, in a Nursing Home for Children of its area. The program aimed to give a better medical-health care and supervision to the population of the mentioned institution. Nursing and medical care was given to the disease problems found and provision made for the follow up. The nurses planned also a health education program for the Sisters with the purpose of improving their ability to participate in the care of the children under their responsability. The evaluation of the work already done showed evidence of good results both for nursing students and nursing personnel as for the people of the institution.